The expanding spaces of law : a timely legal geography - Braverman, Irus, 1970-; Blomley, Nicholas K.; Delaney, David; Kedar, Alexandre (Stanford : Stanford Law Books, 2014)
Legal geography argues that nearly every aspect of law is located, takes place, is in motion, or has some spatial frame of reference. Likewise, every bit of social space, lived places, and landscapes is inscribed with legal significance. Such fragments of a socially segmented world - the where of law - are not simply inert sites; they are also inextricably implicated in how law happens. This volume offers a collection of innovative chapters that extend the reach of legal geography by opening this academic project up to new perspectives, new problematics, new topics, and new voices.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on September 3, 2014).
Keywords: Law and geography; Sociological jurisprudence; Law; Jurisprudence & general issues